Evaluation of electronic medical recording system in Trisuli District Hospital, Nuwakot. (2018)
SUMMARY: Electronic medical recording system that stores the data of patients and other hospital related information electronically is being used globally with the objective of bringing about major changes in health care system, saving health care cost, reducing medical errors and improving performance of health system, electronic medical record (EMR) systems is being widely adopted. In context of Nepal, the Korean and the German government are currently supporting the Ministry of Health and Population (MoHP), Nepal in improving measurement and accountability in Nuwakot District by introducing EMR at the district hospital using open-source technology.Introduction of EMR in health care system of Nepal can be a major push towards evidence based decision making in Nepal. Nepal has its own unique challenges in introducing EMR with very limited use of technology in health care setting, low level of computer literacy, constraints in human and financial resources. Documenting the effectiveness, facilitators, barriers and challenges in implementation of EMR in Trisuli District Hospital can give evidence on whether such program would be effective in other hospitals in days to come. In this context, this study was designed to assess the changes in quality of data after implementation of EMR, readiness of the hospital staffs, potential benefits, facilitators, barriers and challenges in implementation of EMR in Trisuli District Hospital. Mixed method study was carried out that involved Key Informant Interviews and Focused Group Discussion as qualitative method of data collection and face to face quantitative interview and record review as quantitative method of data collection. Study was carried out in two phases: baseline survey that was carried out before implementation of EMR and an endline survey after implementation of EMR. Purposive sampling was be used for selecting participants, from within the TDH, for KIIs and FGDs. There were 18 participants in baseline interview for both KIIs and quantitative interview. The response rate was 100% in baseline study. However in the endline survey, out of total 18 participants approached for participation, 16 agreed to participate and 2 refused participation. Separate readiness assessment tools were used for medical superintendent and other staffs involved in implementation of EMR. Readiness assessment tool used for medical superintendent covered information on organizational alignment, management capacity, operational capacity and technical capacity of the hospital. Readiness assessment tool assessed the readiness of staffs involved in implementation of EMR on Information Technology (IT) skills, organizational support, expected benefits and motivation and understanding about EMR. Each of these domains had multiple questions which were summed to compute the total score in each of these domains. Record review checklist was used for record review.Percentage of missing information in patients' record on ethnicity, age, gender, district, VDC/Municipality and ward. However, the proportion of missing information seems to have increased in case of other variables like investigation and provisional diagnosis was seen after implementation of EMR. Reduction in duplication of task, availability of accurate and updated information, financial transparency, less chance of data loss, prevention of medical errors, reduction in cost of papers and printers, easiness in evaluation of staffs performance and easiness in financial and logistic planning were key benefits that participants shared would be achieved through implementation of EMR. Implementation of EMR also drastically reduced time taken to prepare summary about the patients visiting hospital in a day and reporting time to HMIS 9.4. Relatively more participants in end line study said that they used data in influencing different decision made within the hospital after implementation of EMR. Good team work, willingness of the staffs, commitment from government for sustainability of the program were facilitators in implementation of the EMR while the implementation was hindered by factors like high turnover and frequent transfers of staffs, technical issues like frequent power cutoff, slow server, inadequate backup plan, inadequate manpower for regular repair and maintenance. Participants also shared their experience that patients feel that they are not being paid attention while health personnel consistently look into computer screen for profile of patients and recording of information. Participants suggested that having the system in Nepali language would make it more useful and user friendly. Despite multiple barriers and challenges, implementation of EMR seems to have positive impact on quality of data, use of data in decision making process and improving efficiency in hospital.